A Photovoice Study Exploring Deaf Students Experiences during The COVID-19 Pandemic - Alfina Fadilatul Mabruroh; Gunarhadi Gunarhadi; Herry Widyastono (STAI Hubbulwathan Duri, 2022)
The Indonesia government through Large-Scale Social Restrictions (PSBB) policy urges distance learning with no exception distance learning for all citizens including for deaf students. Students with disabilities may have been harder to adapt to the distance learning. To explore these potential challenges, this study intended to reveal the exeperince deaf student during study from home using photovoice. The participants of this study were 8 deaf students (4 males and 4 females) from 10,11, and 12nd grades Special School in Surakarta. The study revealed three primary findings. Firstly, deaf students felt more convenient to study with the teacher than the parents. Secondly, they expressed their sadness and tedium during distance learning because of no meeting with friends and their teachers. Thirdly, the interviewed students are dread with the Covid-19 in the other hand they have difficulties to enhanced their communication skills and their competences. As the preliminary study, this study's result would be beneficial for future research. The stakeholder or the researcher can be developing meaningful and joyful learning for helping deaf students adapt the distance learning.